2007
DOI: 10.1590/s1678-91992007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion stings in one province of Morocco: epidemiological, clinical and prognosis aspects

Abstract: The present study aimed at verifying the impact of a Moroccan strategy against scorpion stings and, specifically, at identifying the epidemiological features of the patients envenomed or just stung by scorpions. The investigation included 4089 patients from a province of Morocco which were evaluated over three years (2001, 2002 and 2003). Most stings occurred during the hot period and mainly at night (between 6:00 p.m. and 12:00 p.m.). The average incidence was 2.8‰, the average age of the patients was 26.7&pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
9
0
2
Order By: Relevance
“…Comparison among data from recent years revealed an increased number of reported cases and decreased morbidity and mortality (12).…”
Section: Discussionmentioning
confidence: 97%
“…Comparison among data from recent years revealed an increased number of reported cases and decreased morbidity and mortality (12).…”
Section: Discussionmentioning
confidence: 97%
“…Epidemiological data compiled by the Poison Control and Pharmacovigilance Center of Morocco (CAPM) showed that scorpion stings are the leading cause of poisoning in Morocco with an incidence ranging from 0 to 2.9‰ and an overall casefatality rate of 0.36% up to 5.3% in some areas (3).Ninety percent of the fatal victims were younger than 15 years old (1). According to the data from the national strategy against scorpion stings, approximately 25,000 stung patients are recorded every year in Morocco (4).…”
Section: Introductionmentioning
confidence: 99%
“…Scorpions play an important role in severe cases of human envenomation in Morocco (10)(11)(12)(13)(14)(15)(16). A previous epidemiological study (10) showed that scorpion stings accounted for 30%-50% of all the poisoning cases reported to the Poison Control Center of Morocco (PCCM) mainly in the south and central-south provinces of the country, where the highest lethality rate was reported.…”
Section: Introductionmentioning
confidence: 99%